Relationship Between Oxidative Stress and Severity of Diabetic Foot Ulcers Among Patients With Type‐2 Diabetes Mellitus in Japan: A Cross‐Sectional Study - Amos Tinashe Nyamadzawo; Junko Nishio; Toshiko Ogawa; Shinobu Okada (Health Science Reports)
ABSTRACT Background Delayed healing of diabetic foot ulcers (DFUs) is associated with significant morbidity, and oxidative stress (OS) induced by a diabetic state is considered an essential factor in the development of DFUs. Aims To determine how systemic OS correlated with the severity of DFUs and to evaluate factors influencing OS in patients with type‐2 diabetes mellitus. Methods Purposive sampling was used to recruit 44 outpatients with type‐2 diabetes (DM) from a hospital's foot care department and 32 attendees without DM from an elderly welfare centre in Japan. Participants' demographic data, medical history, fasting blood sugar, HbA1c, and ABI were assessed at every visit. Also, urinary malondialdehyde (MDA) concentrations were measured to indicate systemic OS. Results Urinary MDA was higher in diabetic patients (p < 0.001). The presence of DFUs was associated with significantly elevated urinary MDA (p < 0.001) among diabetic patients. There was a strong correlation between worsening DFU severity and increasing MDA levels (rs (19) = 0.708, p < 0.001). Glycaemic control (p = 0.015) and ABI (p = 0.035) were also related to DFU severity. Diabetic state (p < 0.001) and poor glycaemic control (p < 0.001) coincided with elevated urinary MDA concentrations. Conclusion Higher systemic OS in a diabetic state and a strong correlation between wound severity and urinary MDA indicate that OS induced through several mechanisms relating to the diabetic state plays a vital role in DFU. Thus, OS can be a viable target for wound management in diabetic patients.